Analysis of Personality and Local Culture: The Effect on Employee Performance - Irwan Idrus; Andi Fitriani; Hajriana Hajriana (UPT Penerbitan Universitas Jember, 2021)
The purpose of this study is to analyze: the effect of personality on employee performance of Population and civil registry office of Pinrang; the effect of local culture on employee performance of Population and civil registry office of Pinrang; the effect of personality and local culture simultaneously on employee performance of Population and civil regsitry office of Pinrang. The data collection techniques used in this study were observation, interviews, and questionnaires. The sample used in this study were 90 respondents who were employees of Populaation and civil registry office of Pinrang. The data analysis method used is multiple linear regression analysis, using the SPSS program. It is found that personality has a significant effect on employee performance of Population and civil registry office of Pinrang; local culture has a significant effect on employee performance of Population and civil registry office of Pinrang; personality and local culture simultaneously have significant effect on employee performance of Population and civil registry office of Pinrang. Keywords: Employee Performance, Local Culture, Personality.